Smoking in Brazil - Deborah Carvalho Malta; Crizian Saar Gomes; Fabiana Martins Dias de Andrade; Nádia Machado de Vasconcelos; Elton Junio Sady Prates; Cimar Azeredo Pereira; Antonio Aurelio de Paiva Fagundes Junior (Universidade Federal de Minas Gerais, 2023)
Introduction: Tobacco use through its different forms continues to be one of the leading preventable causes of death in Brazil. As a remarkable success story, Brazil has achieved one of the largest significant declines in smoking prevalence since 1990. However, worryingly, the rate of decline in tobacco consumption has decreased in recent years, as suggested by surveys. Objectives: The current study aimed to compare the results of three household surveys carried out by the Brazilian Institute of Geography and Statistics (IBGE). Methods: We compared the prevalence of tobacco use among informants aged 18 years or older and the percentage of prevalence changes between 2008, 2013, and 2019 using data from 3 surveys:  The Global Tobacco Adult Survey (2008) and the Brazilian National Health Survey (2013 and 2019). In addition, we analyzed the prevalence for Brazil and states according to age, gender, educational level, and race. Results: The prevalence of active smoking decreased by 19% between 2008 and 2013, from 18,2% (95% CI: 17,7;18,7%) in 2008 to 14.7% (95% CI: 14.2;15.2%) in 2013. However, in 2019, the prevalence was 12.6% (95% CI: 12.2;13.0%) revealing a 14.3% reduction. Smoking was higher among low educational levels population, lower income status, and black and mixed race/skin color. Conclusion: The prevalence of smoking has decreased in Brazil in the past three decades. However, recently there has been a reduction in the intensity of decrease, demanding attention and careful analysis of smoking prevention and cessation strategies.